Testing for a Common OECD Phillips Curve - Turner, Dave (OECD Economics Department Working Papers, 1999)
This paper reports estimates of a reduced form relationship explaining inflation in terms of the output gap and import price inflation for most OECD countries. Results are reported both for single equation estimation on a country-by-country basis and using a system estimation technique in order to impose common parameters across countries where such restrictions are consistent with the data. A striking feature of the results is that most of the countries accept a common sacrifice ratio ...